Peri‐Adolescent Ethanol Vapor Exposure Produces Reductions in Hippocampal Volume that are Correlated with Deficits in Prepulse Inhibition of the Startle. (11th April 2013) - Ehlers, Cindy L.; Oguz, Ipek; Budin, Francois; Wills, Derek N.; Crews, Fulton T.
Abstract : Background: Epidemiological studies suggest that excessive alcohol consumption is prevalent among adolescents and may have lasting neurobehavioral consequences. The use of animal models allows for the separation of the effects of adolescent ethanol (EtOH) exposure from genetic background and other environmental insults. In this study, the effects of moderate EtOH vapor exposure, during adolescence, on structural diffusion tensor imaging (DTI) and behavioral measures were evaluated in adulthood. Methods: A total of 53 Wistar rats were received at postnatal day (PD) 21 and were randomly assigned to EtOH vapor (14 hours on/10 hours off/day) or air exposure for 35 days from PD 23 to 58 (average blood ethanol concentration: 169 mg%). Animals were received in 2 groups that were subsequently sacrificed at 2 time points following withdrawal from EtOH vapor: (i) at 72 days of age, 2 weeks following withdrawal or (ii) at day 128, 10 weeks following withdrawal. In the second group, behavior in the light/dark box and prepulse inhibition (PPI) of the startle was also evaluated. Fifteen animals in each group were scanned, postmortem, for structural DTI. Results: There were no significant differences in body weight between EtOH and control animals. Volumetric data demonstrated that total brain, hippocampal, corpus callosum but not ventricular volume were significantly larger in the 128‐day‐sacrificed animals as compared to the 72 day animals. The hippocampus was smaller and the ventricles larger at 128 days as compared to 72 days, in the EtOH‐exposed animals, leading to a significant group × time effect. EtOH‐exposed animals sacrificed at 128 days also had diminished PPI, and more rears in the light box were significantly correlated with hippocampal size. Conclusions: These studies demonstrate that DTI volumetric measures of hippocampus are significantly impacted by age and peri‐adolescent EtOH exposure and withdrawal in Wistar rats.